Modification And Improvement Of ‘Khao Kriap Waue' (A Traditional Thai Glutinous Rice-Based Snack Food) - Jomduang, SomChai (1994)

(untitled)
' Khao Kriap Waue' (KKW) is a popular Thai snack food made from glutinous rice . Traditional KKW mainly constitutes carbohydrate (92.8%) since its major ingredients are glutinous rice and sugar. I ts other chemical constituents are 5.7% protein, 0.7% fat, 0.6% ash and 0.2% crude fibre. KKW has a l ow fat content and differs from other deep fried snack foods in that it is puffed by roasting, not deep frying. The production of K KW requires several elaborate steps. The glutinous rice grain is soaked, steamed and then pounded with sugar ( sucrose), water and caramel to a moisture content of about 50%. The sticky dough is then made into balls and manually rolled flat, before sun drying. The intermediate moisture product can be stored for less than a week at room temperature and is puffed by roasting on a direct flame before serving.